Effects of a Mindfulness-Based Intervention on Male Portuguese Prisoners - Carmo, Cláudia (International journal of offender therapy and comparative criminology, 2024)
Mindfulness-based interventions (MBIs) in prison environments have revealed positive benefits for prisoners’ physical and psychological health. This study aimed to verify the efficacy of an MBI program in decreasing depressive symptoms, anxiety, stress, negative effects, and increasing positive affects, self-esteem, and mindfulness state and capacity in prisoners. The sample comprised 44 Portuguese male prisoners, who were divided into two groups: the mindfulness training group (n = 22) and the control group (n = 22). The mindfulness training group demonstrated increased self-esteem and mindfulness capacities. Qualitative analysis showed the usefulness of the training for inmates, not only in their daily prison life, but also post-release and the importance of breathing in coping with anxious and stressful situations. These findings suggest the benefits of MBI in prison settings and propose that these interventions may hold the potential to improve prisoners’ reintegration into society.